The amazing Mexican secret - Greenhut, Josh (Flat Stanley's worldwide adventures., 2010)
Confident that Stanley can succeed where international spies and thieves have failed, Stanley's mom who loves to cook mails him to Mexico to get a secret herbal ingredient that she must have.